Using the SERVQUAL model to evaluate the quality of services for a farm school store - Michael C. Handrinos; Dimitris Folinas; Konstantinos Rotsios (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
The main objective of this paper is to present and analyse the findings of research which aims to measure the services that a locally-based SME (Small-Medium Enterprise) campus store of a farm school provides to its customers. The examined start-up store is operated by the College students in the context of their entrepreneurship, business and marketing classes. After one year of operation students decided to evaluate the quality of the store's services and measure the customers' satisfaction by applying the well-known SERVQUAL model. The deployment of the model revealed at first the importance of the store know-how to measure services from the consumers' perspective so as to better understand their needs. Secondly, the findings of the research highlighted "Security", "Reliability" and "Empathy" as the most significant dimensions. The findings of this research can help small and medium enterprises to improve the services they provide to their customers by focusing on these three important dimensions.
Keywords: M30; M31; M39; M00; 650; Quality of services; SME store; SERVQUAL; farm school; service provision improvement